Complete Genome Sequence of a thermotolerant sporogenic lactic acid bacterium, Bacillus coagulans strain 36D1. Issue 3 (November 2011) - Rhee, Mun; Moritz, Brélan; Xie, Gary; Glavina del Rio, T.; Dalin, E.; Tice, H.; Bruce, D.; Goodwin, L.; Chertkov, O.; Brettin, T.; Han, C.; Detter, C.; et al.
Abstract Bacillus coagulans is a ubiquitous soil bacterium that grows at 50–55 °C and pH 5.0 and ferments various sugars that constitute plant biomass to L (+)-lactic acid. The ability of this sporogenic lactic acid bacterium to grow at 50–55 °C and pH 5.0 makes this organism an attractive microbial biocatalyst for production of optically pure lactic acid at industrial scale not only from glucose derived from cellulose but also from xylose, a major constituent of hemicellulose. This bacterium is also considered as a potential probiotic. Complete genome sequence of a representative strain, B. coagulans strain 36D1, is presented and discussed.